ALTRUISM AMONG ORGANIC RICE FARMERS IN YOGYAKARTA - Azizatun Nurhayati; I Irham (Agricultural Socio-Economics Journal, 2020)
Organic farming is becoming an issue that continues to grow at this time. Organic products become exclusive products at higher prices compared to conventional agricultural products. The higher price can be one form of motives for farmers to do farming with an organic system that is the economic motive. On the other hand, organic agriculture with environmentally-friendly management is an advantage of this farming system.  It is necessary to know more about the motives of farmers in undertaking organic farming, economic or non-economic motives. Non-economic motives in an agricultural activity are needed to support agricultural activities based on Smart Eco-Bioproduction as an effort to realize sustainable agriculture. The results showed that economic motives still dominated the motives of farmers in organic rice farming. Altruism, as a non-economic motive, is at the level of human altruism.